Correlation between Mucoepidermoid Carcinoma Grade and AgNOR Count - Sobia Siddique,Haffez ud Din ,Shoaib Nayyer Hashmi ,Atiq ur Rehman ,Tahir Khadim (Journal of Rawalpindi Medical College, 2014)
Background: To assess the cellular proliferation rate of major and minor salivary gland mucoepidermoid carcinoma (MECs) by quantitative analysis of AgNOR and to determine its relation to histopathologic grading. Methods: In this descriptive study 30 cases of MEC were included. Histological grading was done and slides were stained for AgNOR counts. Tumours were graded into low, intermediate and high grades. Sections were hydrated in decreasing concentration of alcohol, rinsed in distilled water, and incubated in freshly prepared working solution for 30 min at room temperature in the dark. Sections were then washed in distilled water for 1 min. Toning agent gold chloride was applied for 2 min. Sections were then dehydrated in increasing concentration of alcohol, cleared and mounted in Xylene (DPX) medium. NORs were counted in tumour cells, appearing as brownish black intra-nuclear dots on a pale yellow background. The NORs thus detected indicate the quantity of protein bound to juxtanucleolar ribosomal DNA. AgNOR counts were obtained using a semi-quantitative method; 100 nuclei from each case were randomly examined, silver-stained dots were counted using a x1,000 oil-immersion lens, and the mean number of AgNOR for each epidermoid cell type was determined. Results: Majority (43%) cases were graded as low grade MEC. Most common site was parotid gland (73%) followed by hard palate(13%). Most common age was between 30 years to 60 years (53%) and males were affected most frequently with male to female ratio of 1:0.43.For AgNOR count high grade MEC showed mAgNOR 1.87 ±0.66,intermediate grade MEC 0.74 ±0.28 and low grade MEC as 0.22 ±0.13 respectively.A significant difference was observed in the mean AgNOR counts among the three grades (p< 0.001 ). Conclusion: Low grade MEC is the most common grade among the three grade of MEC and the mean count of AgNOR increases with the worsening grade of MEC. Thus AgNOR is strong prognostic marker for patients with MEC